Crisis Management and Visitor Satisfaction Using Swot Analysis Method Case Study: Marzano Pizzeria During the Covid-19 Pandemic - Awaloedin, Dipa Teruna; Cahyaningrum, Nilam Dwi; Hasanudin, Hasanudin; Pradini, Gagih (Peneliti.net, 2024)
The Covid-19 pandemic has had a significant impact on the tourism industry and related sectors, including restaurants. Pizza Marzano, an international restaurant chain in Indonesia, faced a crisis due to social restrictions, lockdowns, and changing consumer behavior. This paper explores the crisis management strategies implemented by Pizza Marzano during the pandemic, focusing on the measures taken to maintain customer satisfaction. A qualitative research approach was used, with data gathered through interviews and secondary research. The SWOT (Strength, Weakness, Opportunity, and Threat) analysis method was employed to understand the context of the crisis and identify appropriate mitigation strategies. The findings reveal that Pizza Marzano adopted various measures to mitigate the pandemic's impact, such as adhering to health protocols, enforcing capacity limits, and enhancing take-away services. Public Relations (PR) strategies played a crucial role in addressing the crisis, including open communication, transparency, and leveraging social media to build trust. The evaluation of these strategies indicates that the actions taken effectively increased occupancy and maintained customer satisfaction. In conclusion, effective crisis management strategies and the role of PR helped Pizza Marzano withstand the pandemic crisis and reduce the negative impact on customer satisfaction. The insights from this study can guide other businesses in addressing similar crises in the future